Maintenance Strategy for Pressure Vessel at Offshore Platform Using RBI Method - Ali Reza, Muhammad; Zaman, Muhammad Badrus; Siswantoro, Nurhadi (International Journal of Marine Engineering Innovation and Research, 2023)
The increasing complexity of installations and operations of oil and gas facility, the growing public awareness need to ensure higher levels of safety have give a high pressure to designers and operators to find innovative solution to ensure a safe and economically viable operation. RBI is one of the solution can be used. RBI is a popular method and trusted for measure and develop inspection plan also provide many advantage such as plant availability, decrease failure happen, decrease risk level based on its failure and decrease inspection cost caused for production facility. The use of RBI can help in determining the inspection schedule of pressure vessel V-001 at offshore platform. RBI method determine the risk level of the object by calculate the probability of failure and consequence of failure of the object based on API 581. The result obtained for probability of failure V-001 is 0.000127099 (left head), 0.000123717 (shell) and 0.000131098 (right head) and the consequence of failure is 438.934 m2. The risk analysis of V-001 is categorized as medium level with recommendation inspection is 5 years for external inspection and 10 years for internal inspection with recommendation inspection use ultrasonic test, visual test, edy current and radiographic test.